(untitled) (International Seven Journal of Health Research, 2023)
Objective: To analyze the pattern of infant development in indigenous culture according to previous studies. Methods: 42 articles were found and 12 were included in this study. Results: It can be concluded that developmental delay is more related to difficulty in accessing basic health services. Discussion: Language is present around 9-10 months, with children, at 11-12 months of age, trying to understand words and, at 16 months, waiting to produce words. In tribes in Peru and India, crawling was frequent at 12 months and communicative exchange at 8 to 13 months. In teaching and learning, 9- to 10-month-old children from diverse traditional cultural backgrounds learn by imitation, the most common housework actions. Conclusion: In order for there to be a cohesive identification with developmental delay, in addition to prenatal care and child care, parents should be educated about developmental milestones and associate them with Traditional Medicine.